=en - Aulia, Ahmida Rizki; Bram, Barli (JET (Journal of English Teaching), 2020)
Grammar is a crucial element in communication, especially in a second language, and without the organization of grammar, language exchange is intruded. This paper explored grammatical issues in students’ reflective writing. Data were collected from reflective writing products of a number of students belonging to a class of the English Education Master’s Program of Sanata Dharma University, Yogyakarta, Indonesia. The collected data were analyzed to examine grammatical issues encountered by the students using Dulay, Burt, and Krashen’s (1982) surface strategy taxonomy, which covers omission, addition, misinformation, and misordering errors. Results showed there existed 41 errors in total and were distributed in the following categories: 23 errors of others (other types), six omission errors, five addition errors, four misinformation errors, and three misordering errors. It is expected that the findings can assist learners in overcoming grammatical issues so that they can improve their English grammar and writing skills.